Case report: Recurrence of psychosis after the surgical resection and radiation of a temporal lobe astrocytoma - Perekopskiy, David; Zoghi, Shervin; Dobrick, Jenna; Aboud, Orwa; Bourgeois, James Alan (Frontiers in Psychiatry, 2025)
It is estimated that the incidence of first episode psychotic disorder is about 33 people out of 100,000 each year. Beyond primary psychotic illness (e.g., schizophrenia, schizophreniform disorder), some of these patients will develop psychotic disorder due to a complex interplay of genetics, anatomical variations, traumatic brain injury (TBI), environment, substance use, and/or other causes. A small subset of patients will develop psychotic disorder due to a structural anatomic lesion, such as a CNS tumor. Here we present a 35-year-old male with worsening auditory hallucinations after surgical resection and radiation of a right temporal lobe astrocytoma in the setting of co-morbid methamphetamine usage. This case report helps illustrate how a neuroimaging work-up is important for the first incidence of psychotic disorder and how a tumor can produce a psychotic disorder that persists after oncologic treatment. This paper adds to the literature on the presentation and treatment of post-resection tumor-induced psychotic disorder.